Spatio-temporal drought assessment and comparison of drought indices under climatic variations in drought-prone areas of Pakistan - Muhammad Bilal Ahmad; Ali Muavia; Mudassar Iqbal; Abu Bakar Arshed; Muhammad Mansoor Ahmad (Journal of Water and Climate Change, 2023)
Climatic variations cause droughts which badly affect the environment. The study focused on monitoring droughts to aid decision-making and mitigate their negative impacts on water availability for agriculture and livelihoods in the face of increasing water demand and climate change. To assess the agricultural droughts, a new agricultural Standardized Precipitation Index (aSPI) was calculated which is not used earlier in Balochistan. Widely recommended Standardized Precipitation Index (SPI) and Standardized Precipitation Evapotranspiration Index (SPEI) were used for meteorological drought assessment. Drought indices comparison was also conducted to check the applicability. Rainfall, maximum temperature, and minimum temperature data (1992 to 2021) were utilized to calculate SPI, aSPI, and SPEI at different timescales (3, 6, 9, and 12 months) using DrinC software and SPEI calculator. Indices results revealed the following severe to extreme drought years: 1998, 1999, 2000, 2001, 2002, 2004, 2008, 2011, 2014, 2016, and 2017. It was determined that Dalbandin, Quetta, Sibi, Kalat, Khuzdar, and Zhob experienced higher extreme drought frequencies. Both long- and short-term drought durations were observed. Indices comparison showed that SPI is the most efficient drought index compared to aSPI and SPEI. This study offers valuable insights for managing water resources in the face of climate-induced droughts. HIGHLIGHTS This study reviews the literature studies on different drought indices.; Indices of aSPI, SPI, and SPEI were used for the drought assessment.; A comparison was made between the indices to select the best index.;